Effect of illumination and applied potential on the electrochemical impedance spectra in triple cation (FA/MA/Cs) 3D and 2D/3D perovskite solar cells - Sumayya M. Abdulrahim (17191288) (2021)
Even though there has been numerous works performed based on electrochemical impedance spectroscopy (EIS) of perovskite solar cells (PSCs), however, many aspects of the obtained EI spectra are yet to be fully grasped. Moreover, the change of these spectra over the passage of time needs to be fully analysed and understood, therefore, this research aimed to perform a comparative study to provide a comprehensive understanding of the illumination and voltage dependence of impedence spectra of 3D & 2D/3D PSCs with aging time. The analysis was performed over the period of 5000 h of exposure of the PSCs to the ambient environment at room temperature (24 ± 1 °C). Complex EIS curves (nyquist plots and bode plots) have been investigated (with aging) in the dark, under 1 Sun illumination and at different applied potentials. Over the course of time, the charge transfer resistance (Rct) trend of both solar cells types was observed to be behaving oppositely in the dark and under illumination in the short circuit condition. Moreover, at high potentials in dark conditions, a negative capacitance feature was observed, while under 1 Sun illumination, this feature was realized even at low potentials. All of these complex observations have been interpreted and explained in terms of the charge dynamic in bulk and at the interfaces of 3D and 2D/3D PSCs. This study paves the way to understand further the complex charge dynamic processes within PSCs that evolve under different operating conditions with aging. Other Information Published in: Journal of Electroanalytical Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jelechem.2021.115800